Suprascapular nerve entrapment syndrome caused by a spinoglenoid notch cyst with a concomitant giant lipoma: a case report - Ma, Zaichao; Guan, Mengxue; Abudukadier, Maimaitiyibubaji; Han, Xiaoping; Huang, Tao; Yang, Zengqiang; Li, Biao; Cui, Yong (Frontiers in Surgery, 2026)
BackgroundSuprascapular nerve entrapment is a cause of shoulder pain and dysfunction, often complicated by symptomatic overlap with other shoulder pathologies. Entrapment most commonly occurs at two anatomical constrictions: the suprascapular notch and the spinoglenoid notch. Compression of the nerve's inferior branch at the spinoglenoid notch by a paralabral cyst, leading to isolated infraspinatus weakness and atrophy, is a relatively common pattern. Diagnosis relies on a detailed physical examination, multimodal imaging evaluation including MRI and ultrasound, and confirmation by electromyography. For patients who do not respond to conservative management or who have definitive space-occupying compression, surgical decompression is an effective treatment option.Case presentationThis is the case of a 27-year-old man presenting with progressive right shoulder weakness and pain over just one month, already demonstrating isolated infraspinatus atrophy. Imaging revealed the etiology to be a paralabral cyst that, notably, occupied both the suprascapular and spinoglenoid notches, creating a “double-crush” compression on the suprascapular nerve. This case clearly illustrates how a strategically located space-occupying lesion can lead to rapid and characteristic neurologic deficit, even within a short clinical course.ConclusionThis case clearly illustrates the classic presentation of an isolated spinoglenoid notch cyst causing suprascapular nerve compression, underscoring that this diagnosis must be considered in patients with isolated external rotation weakness even without a clear traumatic etiology, and highlighting that early recognition and systematic evaluation are key to successful management and neurological recovery.